PROTECTING NETWORKS FROM ATTACKS USING ARTIFICIAL INTELLIGENCE - Ismoilov, Sirojiddin Rasuljon o‘g‘li; Shamamatova, Sayyora Jo‘raboy qizi; Maxmudov, Ulug‘bek Ravshanbekovich (Educational Research in Universal Sciences, 2024)
Network attacks are a growing threat to businesses and organizations of all sizes. Traditional security measures, such as firewalls and intrusion detection systems (IDS), are no longer sufficient to protect against the latest and most sophisticated attacks. Artificial intelligence (AI) offers a promising new approach to network security. AI-based systems can learn from historical data to identify patterns of behavior that are associated with attacks. This allows them to detect new and emerging threats that traditional security measures cannot see.